SPIRITUAL TOURISM AND GENEROSITY: THE INFLUENCE OF WALI SHRINES' PILGRIMAGE ON ALMSGIVING IN EAST JAVA, INDONESIA - Mahatva Yoga Adi Pradana; Muhammad Al Fayyadh Maulana; Muhammad Mansur (Penamas, 2025)
This article explores how Wali pilgrimage tourism influences the formation of pilgrims' attitudes toward charity in East Java. This study aims to understand how the spiritual experiences and cultural values associated with the Wali pilgrimage site can shape pilgrims' socio-religious behavior. Data were collected through in-depth interviews, participatory observations, and documentation at key pilgrimage sites in East Java. The findings reveal that Wali pilgrimage tourism is not only a form of religious fulfillment but also enhances pilgrims' awareness and commitment to charity through almsgiving. The management of pilgrimage sites that blend Islamic values with local culture plays a crucial role in fostering a spiritual environment conducive to generosity. Local leaders and community figures serve as catalysts in reinforcing social and religious values that promote community solidarity. This research highlights the significance of spiritual tourism as a tool for cultivating positive social attitudes and offers insights for the sustainable development of religious tourism in Indonesia. Consequently, ongoing efforts to strengthen spiritual and social values within pilgrimage tourism are essential to maximize its positive community impact.